The hygienic assessment of modern sources of light - T. V. Andropova; L. P. Volkotrub (Бюллетень сибирской медицины)
This article summarizes the current state of electric lighting systems. Comparing characteristic of different electric sources of light allows to reveal there technical, economical and hygienic advantages. There have been recommended the spheres of application of main types of electric light sources.